Sex Differences in the Renal Vascular Responses of AT1 and Mas Receptors in Two-Kidney-One-Clip Hypertension. (20th February 2021) - Pezeshki, Zahra; Nematbakhsh, Mehdi
Abstract : Background . The prevalence and severity of hypertension, as well as the activity of the systemic and local renin angiotensin systems (RASs), are gender related, with more symptoms in males than in females. However, the underlying mechanisms are not well understood. In this study, we investigated sex differences in renal vascular responses to angiotensin II (Ang II) administration with and without Ang II type 1 and Mas receptor (AT1 R and MasR) antagonists (losartan and A779) in the 2K1C rat model of renovascular hypertension. Methods . Male and female 2K1C rats were divided into 8 experimental groups (4 of each sex) treated with vehicle, losartan, A779, or A779+losartan. Responses of mean arterial pressure (MAP), renal blood flow (RBF), and renal vascular resistance (RVR) to Ang II were determined. Results . In both sexes, the basal MAP, RBF, and RVR were not significantly different between the four groups during the control period. The Ang II administration decreased RBF and increased RVR in a dose-related manner in both sexes pretreated with vehicle or A779 (P dose < 0.0001 ), but in vehicle pretreated groups, RBF and RVR responses were different between male and female rats (P group < 0.05 ). AT1 R blockade increased RBF and decreased RVR responses to Ang II, and no difference between the sexes was detected. Coblockades of AT1 R and MasR receptors increased RBF response to Ang II significantly in males alone but not in females (P group = 0.04 ). Conclusion . The impact of Ang II on RBF and RVR responses seems to be gender related with a greater effect on males, and this sex difference abolishes by Mas receptor blockade. However, the paradoxical role of dual losartan and A779 may provide the different receptor interaction in RAS between male and female rats.